2019
DOI: 10.1002/msc.1416
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effectiveness of lateral versus posterior approach to shoulder injection in patients with subacromial impingement syndrome: A pragmatic randomized controlled trial

Abstract: Objective The aim of the study was to determine the effectiveness of the lateral approach to subacromial injection, compared with the posterior approach, for the treatment of subacromial impingement syndrome. Method A pragmatic randomized controlled trial was carried out in an outpatient community musculoskeletal service. The sample comprised 80 adults, aged 18 years or over, with subacromial impingement syndrome. The intervention group received a single subacromial injection, using a 21‐gauge green needle, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Different opinions have been reported about the efficacy of SA injection in studies where the combination of local anesthetic and CS is performed. 13,18,19 While some of these studies reported that methylprednisolone treatment injected into the SA cavity did not affect pain and functional recovery during the 12week follow-up period, 2 different studies concluded that SA injections were effective. 13,18 In one of these studies, Ogbeivor et al reported that VAS and SPADI values were found to be significantly lower at the end of 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different opinions have been reported about the efficacy of SA injection in studies where the combination of local anesthetic and CS is performed. 13,18,19 While some of these studies reported that methylprednisolone treatment injected into the SA cavity did not affect pain and functional recovery during the 12week follow-up period, 2 different studies concluded that SA injections were effective. 13,18 In one of these studies, Ogbeivor et al reported that VAS and SPADI values were found to be significantly lower at the end of 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…13,18 In one of these studies, Ogbeivor et al reported that VAS and SPADI values were found to be significantly lower at the end of 12 weeks. 19 On the other hand, Sumanont et al emphasized that although the CS injection on the shoulder region provided an acceptable reduction in pain and improvement in functional outcomes, the current literature in this area was insufficient. 2 In our study, with the literature, we found that the efficacy of the injection decreased after the 12 th week in the group that received only SA injection.…”
Section: Discussionmentioning
confidence: 99%
“…The nine dimensions for assessing the level of pragmatism in a trial, as proposed in the pragmatic-explanatory continuum indicator summary 2 (PRECIS-2) tool (Adopted from Loudon et al, 2015) used in a pragmatic RCT in a community MSK trial on shoulder pain (Ogbeivor et al, 2019).…”
Section: Figurementioning
confidence: 99%
“…Subacromial Impingement Syndrome results in decreasing range of motion and affecting the functional capabilities and quality of life of the patient 4 . The pain specifically in the anterolateral acromial area is the most typical sign of subacromial impingement syndrome, which radiations maybe felt up to the lateral side of mid portion of humerus bone 5 .…”
Section: Introductionmentioning
confidence: 99%